Evaluasi Strategi E-Commerce sebagai Upaya Penguatan Ekonomi pada Himpunan Pengusaha Pribumi Indonesia - Heri Kusmanto; Warjio Warjio; Evi Yunita Kurniaty (Universitas Medan Area, 2022)
Digitalization is an important need, during the pandemic there is an increase in consumer demand for e-commerce, digital literacy, and delivery requests. This is felt in the Micro, Small and Medium Enterprises of food and beverages through the increasing demand for take away, delivery, and e-commerce sales. The understanding of Micro, Small and Medium Enterprises actors on technology, limited online marketing, production processes, and online market access are still considered not optimal enough. On the other hand, consumers feel insecure in conducting digital transactions. The production sector must foster awareness and build a framework of thinking on business strategies in e-commerce, namely producing competitive products, targeted promotions and creativity in product delivery, while management must provide knowledge of e-commerce law. , regarding trademark protection, electronic payments, obligations and responsibilities of e-commerce actors. The conclusion that the authors get is that the evaluation of the strategy of the Micro, Small and Medium Enterprises of the Indonesian Indigenous Entrepreneurs Association in e-commerce is that there is no proper e-commerce business strategy for Micro, Small, and Medium Enterprises which results in problems or obstacles in supporting business digitization. Micro, Small, and Medium.